Effect of sewage sludge and digestate from anaerobic fermentation on the accumulation of cadmium (Cd), gallium (Ga), germanium (Ge), and rare earth elements (REEs) in soil and uptake by plants with different nutrition strategies - Nazia Zaffar; Viktoriia Lovynska; Viktoriia Lovynska; Alla Samarska; Tobias Arnstadt; Olivier Pourret; Stéphan Firmin; Petr Baroš; Eliška Lyko Vachková; Martin Palušák; Stanisław Wacławek; Edgar Peiter; et al. (Frontiers in Environmental Science)
This study investigates how sewage sludge and liquid digestate, as biosolid amendments, affect the mobility of cadmium (Cd), gallium (Ga), germanium (Ge), and rare earth elements (REEs) in soil, as well as their uptake by plants with differing nutritional strategies. Four species Alyssum murale, Lupinus albus, Fagopyrum esculentum, and Carthamus tinctorius were cultivated on unamended soil or soil amended with either sewage sludge or digestate. Shoot uptake of the essential elements P, Fe, Mn, Ni and of non-essential elements was evaluated alongside changes in ammonium-acetate-extractable (labile) element concentrations. For three species, root carboxylate exudation and rhizosphere acidification were also measured under variable phosphorus (P) supply conditions induced by the amendments. Both biosolids improved micronutrient availability across all species. However, increased shoot P concentrations were only observed in plants treated with sewage sludge. Digestate addition elevated total Ge (14.4%), labile Ga (178%), and labile REE (22%) concentrations in soil, while sewage sludge increased labile Cd (31%) and decreased labile REEs (18%) concentration. Neither amendment enhanced Ge uptake by plants. A higher proportion of labile Cd correlated with a higher Cd uptake in all tested plant species. However, the shoot net uptake of Ga and REE did not reflect their mobility in soil. More specifically, a higher Ga mobility in soil only increased Ga uptake in F. esculentum. F. esculentum acidified the rhizosphere and released fewer carboxylates under conditions of high P supply. Despite lower labile REEs concentrations in sewage sludge amended soil, L. albus and F. esculentum accumulated more REEs when the P supply was increased due to biosolids addition. The findings highlight that while Cd transfer is predictably linked to its labile soil pool, the uptake of Ge, Ga, and REEs depends on complex interactions between soil chemistry and plant-specific physiological traits responses to biosolid-derived nutrient inputs.